2012
DOI: 10.1007/s00383-012-3081-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel t(3;8)(p13;q21.1) translocation in a case of lipoblastoma

Abstract: Lipoblastoma is a rare benign neoplasm of embryonic white fatty tissue primarily found in the extremities of children <3 years old (Batanian et al., Cancer Genet Cytogenet 125(1):10-13, 2001; McVay MR et al., J Pediatr Surg 41(6):1067-1071, 2006; Kamal et al., J Pediatr Surg 46(7):E9-E12, 2011). Translocations affecting the 8q11-13 region are commonly reported with lipoblastoma and proper diagnosis requires cytogenetic analysis to distinguish it from malignant myxoid liposarcoma (Miller et al., J Pediatr Surg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Miller et al showed a similar breakpoint in the long arm of chromosome 8 within a lipoblastoma. Brinkman et al more recently discovered a novel t(3,8)(p13;q21.1) translocation in a case of lipoblastoma. In contrast, myxoid liposarcomas are characterized by the specific clonal chromosomal translocation t(12,16)(q13;p11) , which is not seen in lipoblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Miller et al showed a similar breakpoint in the long arm of chromosome 8 within a lipoblastoma. Brinkman et al more recently discovered a novel t(3,8)(p13;q21.1) translocation in a case of lipoblastoma. In contrast, myxoid liposarcomas are characterized by the specific clonal chromosomal translocation t(12,16)(q13;p11) , which is not seen in lipoblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…10 Another alternative oncogenic mechanism is polysomy 8 and t(3; 8) (p13; q21.1). 11 No malignant degeneration has been documented while a high recurrence rate has been described in lipoblastomatosis and incomplete resections. 2 Complete resection is the only curative treatment and it should not be delayed when the compression of surrounding structures is imminent.…”
Section: Discussionmentioning
confidence: 99%
“…These are potentially related to larger chromosome 8q alterations that include the PLAG1 gene [ 4 , 7 , 46 ]. PLAG1 fusion gene partners described in lipoblastoma include HAS2 (8q24.13), COL1A2 (7q21.3), RAD51B (14q24.1), COL3A1 (2q32.2), RAB2A (8q12.1–q12.2), BOC (3q13.2), DDX6 , KLF10 , KANSL1L , ZEB2 and EF1A1 [ 38 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. HMGA2 alterations are less common [ 38 , 42 ].…”
Section: Lipoblastoma and Lipoblastomatosismentioning
confidence: 99%